DU CONFLIT AU TERRORISME EN RD CONGO - URS, Andreea Bianca (Studia Universitatis Babes-Bolyai Studia Europaea, 2020)
From Conflict to Terrorism in DR Congo. A wind of terror has been revealed in Beni territory since November 2019, when a series of mysterious massacres attributed to the Allied Democratic Forces movement (ADF or ADF-Nalu) restarted. For the past two decades the Eastern territory of the Democratic Republic of Congo has been the main target of several bloody conflicts among which the last one is about ADF. Furthermore, the upsurge of ADF massacres was accompanied by a propaganda campaign built around jihadist discourse. Terrorism represents a real contemporary threat for the DRC, but not in its Islamist form as envisaged by the government. This paper aims to analyze the instrumentalization of terrorism in the DRC as well as the steps which have transformed the conflict into terrorism.